2013
DOI: 10.3928/1081597x-20130129-07
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Error Assessment: Influence of Different Optical Elements and Current Limits of Biometric Techniques

Abstract: The most relevant optical elements either do not have available measurement instruments or the existing instruments still need to improve their accuracy. Ray tracing can be used as an optical assessment technique, and may be the correct path for future personalized refractive assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…The mean difference found is relevant, since a 1 mm error in AL results in a residual postoperative refractive error of 2.35 D in a 23.5 mm eye, 1.75 D in a 30.0 mm eye and 3.75 D in a 20 mm eye or about 2.0–4.0 D in the power of the implanted IOL. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean difference found is relevant, since a 1 mm error in AL results in a residual postoperative refractive error of 2.35 D in a 23.5 mm eye, 1.75 D in a 30.0 mm eye and 3.75 D in a 20 mm eye or about 2.0–4.0 D in the power of the implanted IOL. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Although the keratometry evaluation methods are different, there is a close relationship between the values reported in Caucasian populations, which are generally lower than in the Far Eastern populations. The difference observed with respect to Far Eastern populations is significant, representing a potential difference in the refractive error greater than 0.50 D. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Ribeiro et al (12) they evaluated the changes of each optical parameter on the refractive state of the eye and found that a 0.25 mm change in ACD measurement corresponds to an error of 0.10 D in an eye with an NA of 30.0 mm and 0.50 D in an eye with an AL of 20.0 mm. Following these results, studies were carried out assessing various ranges of ACD values to evaluate which formula was more effective.…”
Section: Discussionmentioning
confidence: 99%
“…In an older population, as is often the case in the cataract population, the lens is thickened and therefore the depth of the ACD is shallower. Ribeiro et al (12) found that for every 1% increase in lens thickness, the refractive error changes by 0.097, a 0.104 mm change in LT means a 0.25 D change in refractive error. Studies have already been published relating the different ocular parameters, including LT and the prediction error of the different formulas (16, 17).…”
Section: Discussionmentioning
confidence: 99%
“…Los modelos personalizados obtenidos con una finalidad óptica están basados fundamentalmente en técnicas de tratamiento de imágenes obtenidas de un OCT, pudiendo así cuantificar la influencia del espesor corneal en el índice de refracción (Lai y Tang, 2014), o la influencia de la inclinación y del descentrado de una lente intraocular en la potencia corneal (Einighammer et al, 2009;Ribeiro et al, 2012;Wang et al, 2013). Otros equipos, como los biómetros, se pueden utilizar para medir la potencia corneal a partir de las imágenes generadas por éstos (Ribeiro et al, 2013). Figura 1.8 Modelos personalizados.…”
Section: Caracterización a Partir De Técnicas De Tratamiento De Imágenesunclassified